IMPLEMENTASI PROJECT BASED LEARNING, CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN KOMPETENSI MAHASISWA - Annisa Fatimah; Marlina Magdalena; Suryadi Suryadi; Ima Kristanti (JURNAL ILMIAH EDUNOMIKA, 2024)
The aim of this research is to implement a learning model during lectures that integrates Project Based Learning (PjBL) and Contextual Teaching and Learning (CTL) in the Computer Accounting course. This learning strategy makes it possible to produce qualifications for graduates' abilities starting from their attitudes, knowledge and skills in accordance with national higher education standards. It is proven that through the combination of PjBL and CTL, students can relate the material to real world situations, thus motivating students to make connections between knowledge and application in real life using projects as a medium. Student involvement in this project is their "research" area, starting from finding possible problems, analyzing the problem and drawing conclusions or finding solutions. The results of the research show that there are changes in students' learning behavior and social communication skills which can be seen in the assessment rubric through completing the assignments given. This combination of learning models is considered to be in accordance with the character of adult education (adult learning) which can motivate oneself by using the experience and knowledge gained so that the results can be oriented towards achievement and the relevance of the material through an independent learning process adapted to different types of learning styles.